2009
DOI: 10.1097/dbp.0b013e3181aac6e4
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Effects of Deployment on Military Children

Abstract: Families in this study experiencing deployment identified one-third of military children at "high risk" for psychosocial morbidity. The most significant predictor of child psychosocial functioning during wartime deployment was parenting stress. Military, family and community supports help mitigate family stress during periods of deployment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
234
3
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(250 citation statements)
references
References 23 publications
10
234
3
3
Order By: Relevance
“…Our results add to the findings of recent previous studies that documented deployment-related changes in child behavior by linking them to clinically apparent psychological and behavioral issues that merit the clinical attention of a pediatric provider. 14,16 Previous research has documented the differences between paternally and maternally separated children. 19 One possible explanation is that the mothers remaining at home may be more likely to manifest their own mental health issues or that mothers are more likely to transfer their own mental health symptoms onto the child.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results add to the findings of recent previous studies that documented deployment-related changes in child behavior by linking them to clinically apparent psychological and behavioral issues that merit the clinical attention of a pediatric provider. 14,16 Previous research has documented the differences between paternally and maternally separated children. 19 One possible explanation is that the mothers remaining at home may be more likely to manifest their own mental health issues or that mothers are more likely to transfer their own mental health symptoms onto the child.…”
Section: Discussionmentioning
confidence: 99%
“…The age range of 3 to 8 years was chosen because it excluded the younger ages at which there are frequent well-child visits, corresponded to the ages included in previous studies that documented subclinical behavior changes, and included the developmental stage at which one of the authors (Dr Gorman) had observed an increase in behavioral concerns in his pediatric practice. 14,16 Children of National Guard or Reserve personnel were excluded. Each subject's demographic information and enrollment date were extracted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reinforcement is more readily available for families when they live on or close to the defense base (Brooks, 2011), which is particularly important for those without extended family nearby because access to parental support also affects the children. Flake et al (2009) believed that parenting, resources, supports, and resilience influence children's psychosocial functioning during the deployment cycle.…”
Section: Protective Factors Provided By Relationships (Microsystem)mentioning
confidence: 99%
“…Maladaptive parental coping or distress may be the single most important predictor of child biopsychosocial symptoms during stressful situations, such as wartime deployment. [7][8][9] Some military families may be at higher risk of distress, especially if they are young, experiencing a first separation, have recently relocated, include a foreignborn spouse, have young children, are junior enlisted (entry pay level), are single parents, or have children with special needs. 4,9 Service members and families who have not anticipated an extended wartime deployment, such as activated National Guard and Reserve personnel, may be especially challenged.…”
mentioning
confidence: 99%